Effect of Mindi Leaf Powder (Melia azedarach L) on Mortality of Anopheles aconitus Instar III Larvae - Atmaja, Tajudin Rahmat Surya; Ratnaningrum, Kanti; Tursinawati, Yanuarita (Universitas Muhammadiyah Semarang, 2016)
Background: Malaria is a disease caused by Plasmodium parasite infection wwhich is transmitted through bite of an Anopheles mosquito. Efforts to control malaria can be carried out in various ways, starting from treatment, prevention, to breaking the transmission chain through vectors, both mosquitoes and larvae. Mindi tree contains Azadiractin compounds which are larvicides. Study aims to determine effect of mindi leaf powder (Melia azedarach L) on mortality of Anopheles aconitus instar III larvae.Methods: A true experimental study with a post test only control group design, the object of research was Anopheles aconitus Instar III larvae. The research was conducted at Laboratory of Parasitology, Faculty of Medicine, Universitas Islam Sultan Agung, Semarang. 20 larvae / 100 ml were used. Air temperature and water pH were controlled during observation. Assessment by counting number of mortality larvae and the number of live larvae from each treatment was compared to the control. The data obtained were analyzed by the Kruskal-Wallis statistical test. The LD50 and LD90 were analyzed using Probit analysis.Results: The dose of 0.2 g/100 ml was the minimum dose that killed 100% of larvae of Anopheles aconitus (p = 0.01). In the probit test, LD50 was 0.01 g/100 ml of aquades, while LD90 was 0.06 gram/ 100 ml of aquades.Conclusion: Dose can served as larvicidal (LD90 )was 0.06 g/100 ml of aquades., while LD50 was 0.01 g/100 ml of aquades.